The Use of Gamification (Kahoot!) to Increase Vocabulary Mastery in Elementary School - Khoirunnisa, Silmi; Farah, Rafika Rabba (International Journal of Learning Reformation in Elementary Education, 2025)
This study investigates the effectiveness of gamification, specifically through the use of Kahoot!, in enhancing vocabulary mastery among elementary school students. Employing a quasi-experimental design, the research involved 36 learners from SD Negeri 01 Pandian, consisting of 18 students from grade 6A as the experimental group and 18 students from grade 6B as the control group. Data were gathered through pre-test and post-test vocabulary assessments, accompanied by student questionnaires designed to capture levels of engagement and motivation during the learning process. Quantitative data were analyzed using IBM SPSS Statistics 22. Paired sample t-tests were conducted to measure within-group differences, and independent sample t-tests were applied to compare learning outcomes between the two groups. The findings indicate that Kahoot! significantly improved students’ vocabulary achievement, as evidenced by a (Sig.) (2-tailed) value of 0.000 < 0.05. The experimental group’s mean score increased markedly from 45.78 (pre-test) to 86.22 (post-test), while the control group showed a smaller improvement from 39.56 to 63.11. These results demonstrate substantial gains in the group exposed to gamified learning, leading to the rejection of the null hypothesis (H₀) and acceptance of the alternative hypothesis (Hₐ). This confirms that the integration of Kahoot! positively influences vocabulary mastery among sixth-grade students. The study highlights the pedagogical potential of gamification in elementary education, suggesting that Kahoot! can be effectively incorporated into daily instructional activities to boost student engagement and vocabulary development. It contributes to the growing literature on digital learning tools, highlighting their role in creating interactive and engaging learning environments.